Somewhere safe with somebody good - Karon, Jan, 1937- (Karon, Jan, 1937- Mitford years, 2014)
"After five hectic years of retirement from Lord's Chapel, Father Tim Kavanagh returns with his wife, Cynthia, to Mitford where he - and his beloved friends and family - face the challenge of settling into the next phase of their lives"--